“Já veio tudo dos antepassados": História, memória e identidade étnica em Caiana dos Crioulos - Lima, Herzom Vieira Costa (2015)
How can we define a maroon? This issue is the main issue of this paper. Therefore, we draw as the object of our research, community of Caiana dos Crioulos, in the municipality of Alagoa Grande - PB and recognized as a legitimate Community Remnant of Quilombo - CRQs, aiming to understand how the ethnic identity of the residents is articulated at different times and how they perceive themselves as Maroons. In this sense, for the research, we use various media, such as oral sources obtained with five interviewed, belonging to community or linked to it in some way; CDs with records of Cocos and Cirandas; reports conveyed by newspapers at different times and provided an overview of the community before his legitimacy as well as baptisms of books and the 1872 Census regarding discussions concerning the nineteenth century period. Regarding the theoretical framework, we work from the concepts of individual memory and collective memory (Maurice Halbwachs), tradition (Caroline Luvizotto), invented tradition (Eric Hobsbawm and Terence Ranger), identity (Maria Lucia Montes), ethnic groups and ethnicity ( Fredrik Barth), place of memory (Pierre Nora), in addition to document concepts and monuments, proposed by Jacques Le Goff, which were of great relevance to the research, as it led to the understanding of the hypotheses that explain the emergence of the community. Through the obtained reports, realized in the versions on community origin which Hebe Mattos characterized as resistance memory, once all are associated with fight against the slave system and the denial of enforcement captivity imposed by his captors. We also realize that the ancestors occupy a prominent place in the collective memory of the inhabitants, as they contributed to the consolidation of cultural practices and ways of perceiving the world that have become traditions and that older residents seek reproduce, passing on to more residents new inheritance of the Maroons. Therefore, the quilombo identity of residents of Caiana dos Crioulos is a field where articulate symbiotically memory and tradition, where the past is constantly elucidated and front reframed the settings of contemporary society.